Teološke kreposti vere, upanja in ljubezni kot temelj človeškosti v odnosu do transhumanizma - Trontelj, Nik (Bogoslovni vestnik, 2024)
In this paper, we seek an answer to the fundamental question: who is a man in relation to transhumanism in its various implications (cyborg, humanoid robot). We follow Christian anthropology, which fundamentally presents man as a physical and spiritual being, i.e. in his or her natural and relational dimension in relation to God, which establishes man as a person. Man's identity is essentially defined by his or her ability to live by the theological virtues of faith, hope and love, which distinguishes him or her apart from transhumanist beings, despite their possible physical and mental superiority to humans. Man longs for the fullness of life, which he or she achieves only in a relationship, not in the context of improving natural abilities. On the basis of our reflection, we have found that there are serious inconsistencies in qualitatively contrasting the transhumanist image of man with the Christian doctrine of man. At the moment of this paper being written, no artificially intelligent being is known to meet the criteria of personhood from the Christian perspective.
Keywords: cyborg; faith; hope; humanoid robot; humanoidni robot; interpersonal relationships; kiborg; ljubezen; love; medosebni odnosi; transhumanism; transhumanizem; upanje; vera